If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(Y + 1) = 1(3Y) Reorder the terms: 2(1 + Y) = 1(3Y) (1 * 2 + Y * 2) = 1(3Y) (2 + 2Y) = 1(3Y) Remove parenthesis around (3Y) 2 + 2Y = 1 * 3Y Multiply 1 * 3 2 + 2Y = 3Y Solving 2 + 2Y = 3Y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-3Y' to each side of the equation. 2 + 2Y + -3Y = 3Y + -3Y Combine like terms: 2Y + -3Y = -1Y 2 + -1Y = 3Y + -3Y Combine like terms: 3Y + -3Y = 0 2 + -1Y = 0 Add '-2' to each side of the equation. 2 + -2 + -1Y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1Y = 0 + -2 -1Y = 0 + -2 Combine like terms: 0 + -2 = -2 -1Y = -2 Divide each side by '-1'. Y = 2 Simplifying Y = 2
| t-8=11 | | 2x+3(4x+3)= | | 5(96/10)+2 | | 3(x-2)=7 | | 2x+3=5x+5/2 | | 2x+10=-1+x | | 10-3x=-6x+25 | | 7(2x)+3(x+4)= | | s=2*3.14rh+2*3.14r(2) | | 8+5ln(x)=6 | | 2y-13=12 | | 4(2x+3y)+2(x+3y)= | | -4x+4=-3-3x | | 3y+(5-2y)= | | -6a+2+7a=11-30 | | 4(5x)+2(3y)-20x= | | 3x+14=82-9x | | 45k=97 | | 2x+8=4(3x-6) | | 9x-190=3x-10 | | a+1.25=2.70 | | m/8=8.33333333333333333333333 | | -5(y-3)+4(y-2)=32 | | -132/390 | | 7x-4=8(x-5) | | -3(x+2)-6=2(x-4)+8 | | 3x+x+2/3x=23 | | a+11/4=27/10 | | 4/3+8/x | | -7/8=2/3+n | | 48/300 | | 4x-3x=3+3x-3x |